SELF-ESTEEM DAN HARDINESS SEBAGAI PREDIKTOR SUCCESSFUL AGING LANSIA YANG TINGGAL SENDIRI - Amaheka, Briskia Grace Augita; Christiana, Soetjiningsih Hari (Mediapsi, 2019)
The purpose of this study is to examine the effect of self-esteem and hardiness on successful aging in the elderly who live alone. This research is a quantitative study with 142 participants who lived alone (at least living with a partner, not with children) in 6 cities in Central Java, which were obtained using a purposive sampling technique. Data were obtained using Successful Aging Scale (Rowe and Kahn), Rosenberg Self-Esteem Scale (Rosenberg) and Short Hardiness Scale (Bartone). The results of this study indicate that simultaneous self-esteem and hardiness as predictors of successful aging in elderly people who live alone (minimum life with a partner, not with children), seen from the obtained Fcount value of 35.963 and Ftable of 2.670 (Fcount > Ftable) and a significance value of 0,000 (p <0,05). That is, this study provides practical implications, namely when the elderly who live alone have high self-esteem and hardiness, it will affect the high successful aging of the elderly in their old age.